VILIUS GAIGALAITIS’ ATTITUDES AND ACTIVITIES IN BOOK SCIENCE - KAUNAS, DOMAS (Knygotyra, 2015)
stillenhandschrift aus dem Jahre 1573” (A manuscript of Wolfenbütteler Lithuanian Postilla published in 1573) that he defended in 1900, a historiographic essay on Lithuanina book in Lithuania Minor “Lithuanian history and our writings” (1912), some chapters in other books and articles in a journal Pagalba (Help) edited by himself. Gaigalaitis always investigated the printed or manuscript heritage de visu. Old manuscripts, books, periodicals, and calendors were primary sources for his research, data analysis, synthesis, and formulation of conclusions. During his studies he developed bibliographic skills and provided bibliographic data to Silvestras Baltramaitis – the librarian of the Imperial Public Library in St. Petersburg, to a serial published by Lithuanian Literary Society in Tilsit, to the professor Vaclovas Biržiška at Kaunas University. In 1905–1939 he headed a cultural-educational society „Sandora“ and established its library of great scientific and cultural significance as well as increased its publishing activity. Gaigalaitis used press as an important means in realisation of strategic political and spiritual goals. He employed Lithuanian press and publications to unite the national community, to ensure its internal communication and develop NATIONAL identity, to ensure its self-expression and public relations.